2007
DOI: 10.1534/genetics.107.070904
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of Gluconeogenesis in Aspergillus nidulans

Abstract: Aspergillus nidulans can utilize carbon sources that result in the production of TCA cycle intermediates, thereby requiring gluconeogenesis. We have cloned the acuG gene encoding fructose-1,6 bisphosphatase and found that expression of this gene is regulated by carbon catabolite repression as well as by induction by a TCA cycle intermediate similar to the induction of the previously studied acuF gene encoding phosphoenolpyruvate carboxykinase. The acuN356 mutation results in loss of growth on gluconeogenic car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
68
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 62 publications
1
68
0
Order By: Relevance
“…Regarding the relationships between RSE2 and RSE3, the observation that the Drse2 rse3 1 , Drse3 rse2 1 , Drse2 rse3 G642 , and rse2 Y300D Drse3 strains are unable to induce the alternative oxidase unambiguously demonstrate that both proteins are required for this induction even when one of them is present in a mutated form. This result agrees with observations reported for N. crassa in which neither the aod2 nor the aod5 mutants are able to induce AOX (Descheneau et al 2005) and in A. nidulans in which neither the acuK nor the acuM mutants are able to induce PCK (Hynes et al 2007). In N. crassa, electrophoretic mobility shift assays showed that AOD2 and AOD5 act synergistically to bind an alternative oxidase induction motif (AIM) present in the promoter of the aod-1 gene, which encodes the alternative oxidase.…”
Section: G303ssupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the relationships between RSE2 and RSE3, the observation that the Drse2 rse3 1 , Drse3 rse2 1 , Drse2 rse3 G642 , and rse2 Y300D Drse3 strains are unable to induce the alternative oxidase unambiguously demonstrate that both proteins are required for this induction even when one of them is present in a mutated form. This result agrees with observations reported for N. crassa in which neither the aod2 nor the aod5 mutants are able to induce AOX (Descheneau et al 2005) and in A. nidulans in which neither the acuK nor the acuM mutants are able to induce PCK (Hynes et al 2007). In N. crassa, electrophoretic mobility shift assays showed that AOD2 and AOD5 act synergistically to bind an alternative oxidase induction motif (AIM) present in the promoter of the aod-1 gene, which encodes the alternative oxidase.…”
Section: G303ssupporting
confidence: 91%
“…Alternative Pathways and Senescence in P. anserinaAcuK in A. nidulans (Hynes et al 2007) act as activators of the expression of genes encoding central enzymes in the gluconeogenic pathway, in particular phosphoenolpyruvate carboxykinase (PCK) and fructose-1,6-biphosphatase (FBPase). PCK catalyzes an early step in gluconeogenesis and converts oxaloacetate to phosphoenolpyruvate, and FBPase catalyzes the final step in hexose monophosphate formation by dephosphorylating fructose-1,6-biphosphate to yield fructose-6-phosphate.…”
Section: Y300dmentioning
confidence: 99%
“…In A. nidulans, the AcuM and AcuK transcription factors form a heterodimer that is a key regulator of metabolic reprogramming in response to gluconeogenic carbon sources (15,16). Previously, we found that in A. fumigatus, AcuM governs not only gluconeogenesis but also iron acquisition (14).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of sreA in the ⌬acuM mutant restored siderophore production and iron uptake in vitro, suggesting that the virulence defect of the ⌬acuM mutant may be due in part to reduced iron acquisition (14). AcuM is also present in Aspergillus nidulans, in which it governs gluconeogenesis but not iron acquisition (14,15). In A. nidulans, AcuM forms a heterodimer with a related transcription factor, AcuK (16).…”
mentioning
confidence: 99%
“…In the presence of long-chain fatty acids, this induction is mediated by FarA and FarB, homologous transcription factors, while a third protein, ScfA, responds to short-chain fatty acids (24). Two other transcription factors, AcuK and AcuM, also regulate gluconeogenic genes and are required for growth on nonfermentable carbon sources (26). AmdX, the closest A. nidulans sequence homolog to ADR1, regulates the acetamidase AmdS, but is not required for growth on a variety of nitrogen or carbon sources (39).…”
mentioning
confidence: 99%